An efficient supramolecular adsorbent for co-adsorption of dyes and metal ions from wastewater and its application in self-healing materials. Issue 46 (13th November 2017) - Yan, Liwei; Lv, Mingqian; Su, Chunjiao; Zheng, Leihao; Li, Jialing; Ye, Zhongbin
Abstract : An efficient adsorbent was prepared for the adsorption of dyes, metals, and dye mixture or binary mixtures of dyes and metals, which could also be used as a self-healing material. Abstract : Herein, a novel type of two-component supramolecular adsorbent, 2 -OA, was developed based on non-covalent interactions using tetrazolyl derivative with octadecylamine (OA) and fully characterized using a number of structural and spectral techniques. The self-assembled2 -OA gels displayed remarkable stimuli-responsiveness as well as shape-persistent and self-healing properties. In addition, it was found that the adsorbent2 -OA was able to remove dyes (10 kinds of cationic and anionic dyes) and metal ions (Cu 2+ and Fe 2+ ) simultaneously from wastewater owing to synergistic electrostatic attraction, hydrogen-bonding, and hydrophobic and coordination interactions. It also exhibited excellent co-adsorption capability to dye mixtures and binary mixtures of dyes and metal ions. In particular, the dye/metal-loaded adsorbents could be obtained easily from the aqueous phase, and recycling of the adsorbents could thus be achieved. These results suggest that the supramolecular gel2 -OA not only has great potential application in wastewater treatment but also provides a strategy for the development of intriguing self-healing materials.